ADSORPTION KINETICS OF Pb , Ni AND Cd ONTO POWDERED EGGSHELLS - Oke, I.A; Fasuyi, Enang; Oloyede, H.O (Ife Journal of Science, 2018)
In this paper, the removal of lead, nickel and cadmium from aqueous solution by adsorption was studied. Chicken's eggshells were collected, washed with distilled water, air dried, pulverized, sieved into different particle sizes and stored for use. Powdered eggshells (PES) were separated, its properties were determined and used as an adsorbent to remove each of these selected metals from aqueous solution individually, multi-componen synthetic wastewater and from natural water in a batch process. Effects of initial concentration of the metals, initial pH of the solution and particle size of PES on the adsorption capacities of these selected metals onto PES were monitored. Estimated cost of producing PES was conducted under two major sources of power supply in Nigeria. The study revealed that PES contained calcium, aluminum, and iron as part of its major components. 2+ 2+ 2+ There were slight reductions in the adsorption of Pb , Ni and Cd onto the larger particle size of PES. Higher adsorption occurred when the initial concentrations and the pH values were increased, but the adsorption capacities were not affected. Cost of PES producing was found to be lower (0.43USD) than the cost of 2+ 2+ producing other adsorbents. It was concluded that PES could be used as an adsorbent to remove Pb , Ni and 2+ Cd from aqueous solutions and raw water